Occupational physical activity in sedentary and active workers - Thompson, Janalee, author; Rosecrance, John, advisor; Anderson, Brooke, committee member; Crain, Tori, committee member (Colorado State University. Libraries, 2017)
With the increasing use of technology in the workplace, many jobs are becoming more sedentary. The purpose of this study was to establish a quantitative baseline measure of occupational physical activity (OPA) in active and sedentary workers. Two activity trackers (Fitbit Charge HR™ and Hexoskin) were used to assess activity measures (step count, heart rate and energy expenditure) among workers during their work shift. The first objective of the study was to assess the agreement between two types of accelerometer-based activity trackers as measures of OPA. The second objective of this study was to assess differences in measures of OPA among workers in physically active and sedentary work environments. There was a statistically significant difference in measures of total step counts between the two devices. When comparing active and sedentary workers there were also statistically significant differences in measures of step counts, mean percent heart rate increase, maximum heart rate range and energy expenditure. Conclusion: The Fitbit Charge HR™ and Hexoskin had significant differences in measures of step counts and heart rate. When comparing active and sedentary workers, there were significant differences in measures of step counts, mean heart rate, maximum heart rate range required by job, and energy expenditure. The results of the present study provide quantitative evidence that active workers require greater physiologic demands than sedentary workers.